Budo: like water lilies in muddy water. (The Voz a Vos Bulletin, 2022)
Budo: como nenúfares en agua turbia is an art research project, made by Cuerpo Testimonio, Dramaturgias Emergentes, that pretends to answer a question about the current pandemic and its consequences in human beings. The project seems to show the necessary attitude we need to confront the accidental beginning of this millennium second decade. The question is: ¿how to be a warrior in contemporaneity? The development of this project is based in the personal research made by every single person of the group, since march of 2020, when the quarantine in Colombia started. Every art piece, product of this research, belongs to the work and intimal vision of each member of Cuerpo Testimonio.
Keywords: Research-creation; warrior; Performing arts